منظوم اردو لغات میں قرآنی الفاظ کا لسانی مطالعہ: Linguistic Study of Qur'ānic words in Versified Urdu Dictionaries (Al-Qamar, 2021)
The compilation of Urdu 'Nisab Name was started in the 16th century AD inspired by Persian Nisab Namé. In view of the specific number of poems in them, it is also called Manzoom Dictionaries. In these courses, Urdu synonym of words in Arabic and Persian languages, which are commonly used in everyday conversation, were included.Khaliq Bari has gotten so much importance in this regard. In Urdu language later on, many dictionaries were written in the style of Khaliq Bari, including Qasida Dar lughat e Hindi, Allah Khudai, Wahid Bari, Allah Bari, Samad Bari, Nisab e Ujab, Khushal ul-Sibyan, Mufid-ul-Bah's, Qadir Nama e Ghalib and The Anglo-Oriental Khaiq Bari. Special importance was given to the words of the Holy Qur'an and their Urdu and Persian interchangeable words were provided in this series of Dictionaries. Later, these words were not only used in Urdu poetry and prose, but also became the basis of their common practice. This article consists of a linguistic study of the same Qur'anic words.
Keywords: Nisab Nama; Manzoom Lughat; Urdu; Quranic Words; Linguistic Study